2019
DOI: 10.3390/polym11071117
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Sesbania Gum-Based Polymeric N-Halamines for Antibacterial Applications

Abstract: Microorganism pollution induced by pathogens has become a serious concern in recent years. In response, research on antibacterial N-halamines has made impressive progress in developing ways to combat this pollution. While synthetic polymer-based N-halamines have been widely developed and in some cases even commercialized, N-halamines based on naturally occurring polymers remain underexplored. In this contribution, we report for the first time on a strategy for developing sesbania gum (SG)-based polymeric N-hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…What is noteworthy is that the introduction of quaternary ammonium salt had the following advantages: (i) increasing the chlorine content from 790 ppm to 6030 ppm because enhanced hydrophilicity of nanofiber materials facilitated the grafting of N -halamine;(ii) changing conductivity of the polymer solution, thus enabling the polymer to be drawn into multi-level nanometer structure containing nanofiber with a diameter of 199 ± 55 nm and nanonets with a diameter of 38 ± 7 nm; (iii) prolong the service life of the materials as a supplementary and stable biocidal group . Plentiful previous researches showed that the antimicrobial material containing N -halamine or quaternary ammonia salt group showed no cytotoxicity [ [26] , [27] , [28] ].…”
Section: Resultsmentioning
confidence: 99%
“…What is noteworthy is that the introduction of quaternary ammonium salt had the following advantages: (i) increasing the chlorine content from 790 ppm to 6030 ppm because enhanced hydrophilicity of nanofiber materials facilitated the grafting of N -halamine;(ii) changing conductivity of the polymer solution, thus enabling the polymer to be drawn into multi-level nanometer structure containing nanofiber with a diameter of 199 ± 55 nm and nanonets with a diameter of 38 ± 7 nm; (iii) prolong the service life of the materials as a supplementary and stable biocidal group . Plentiful previous researches showed that the antimicrobial material containing N -halamine or quaternary ammonia salt group showed no cytotoxicity [ [26] , [27] , [28] ].…”
Section: Resultsmentioning
confidence: 99%
“…Polyacrylonitrile-activated biochar-laccase composite membrane (PAN-BC-LAC) was used as the biocatalytic middle layer for eliminating micropollutants (99% efficiency) and finally an adsorptive membrane enabled reducing color and turbidity. In another study, modification of natural polysaccharide Sesbania gum (SG) was carried out through epoxidation, amination, and chlorination [ 246 ]. Nanofibers of chlorinated SG was then fabricated by electrospinning using polyacrylonitrile (PAN) as the support matrix.…”
Section: Environmental Applicationmentioning
confidence: 99%
“…Although there are some researches on SG in the past several decades, most of them focused on its basic research, and its applications were rarely reported. [ 42–44 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some researches on SG in the past several decades, most of them focused on its basic research, and its applications were rarely reported. [42][43][44] In this contribution, the guanidine polymer was anchored onto sesbania gum through a two-step approach for antibacterial application (Figure 1). Firstly, the o-hydroxyl group on the surface of sesbania gum was oxidized by sodium periodate to achieve the oxidized sesbania gum (OSG).…”
Section: Introductionmentioning
confidence: 99%